Stability of Perovskite Solar Cells: Degradation Mechanisms and Remedies - Mazumdar, Sayantan; Zhao, Ying; Zhang, Xiaodan (Frontiers in Electronics, 2021)
Inorganic–organic metal halide perovskite light harvester-based perovskite solar cells (PSCs) have come to the limelight of solar cell research due to their rapid growth in efficiency. At present, stability and reliability are challenging aspects concerning the Si-based or thin film-based commercial devices. Commercialization of perovskite solar cells remains elusive due to the lack of stability of these devices under real operational conditions, especially for longer duration use. A large number of researchers have been engaged in an ardent effort to improve the stability of perovskite solar cells. Understanding the degradation mechanisms has been the primary importance before exploring the remedies for degradation. In this review, a methodical understanding of various degradation mechanisms of perovskites and perovskite solar cells is presented followed by a discussion on different steps taken to overcome the stability issues. Recent insights on degradation mechanisms are discussed. Various approaches of stability enhancement are reviewed with an emphasis on reports that complied with the operational standard for practical application in a commercial solar module. The operational stability standard enacted by the International Electrotechnical Commission is especially discussed with reports that met the requirements or showed excellent results, which is the most important criterion to evaluate a device’s actual prospect to be utilized for practical applications in commercial solar modules. An overall understanding of degradation pathways in perovskites and perovskite solar cells and steps taken to overcome those with references including state-of-the-art devices with promising operational stability can be gained from this review.